2022
DOI: 10.3390/fermentation8070317
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Functional, and Technological Properties of Protein Hydrolysates Obtained by Microbial Fermentation of Broiler Chicken Gizzards

Abstract: Fermentation is an economical method for obtaining protein hydrolysates. The purpose of the scientific research was to perform a comprehensive analysis of the physicochemical, technological, and functional properties of protein hydrolysates obtained by microbial fermentation. The research results showed that hydrolysates fermented with propionic acid bacteria and bifidobacteria have better physicochemical and technological indicators compared to the control sample. Significant increases in water-holding and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…The results of determining the fat-holding, water-holding and fat-emulsifying capacity are presented in Table 2. The obtained high values of the studied indicators confirmed the literature data on the good technological properties of protein hydrolysates using the example of comparison with the hydrolysate obtained by microbiological fermentation of the broiler chickens gizzard [10]. The values of physical-chemical indicators, as well as their standardized values according to GOST R 55334-2012 "Meat and meat-containing pates.…”
Section: Resultssupporting
confidence: 84%
“…The results of determining the fat-holding, water-holding and fat-emulsifying capacity are presented in Table 2. The obtained high values of the studied indicators confirmed the literature data on the good technological properties of protein hydrolysates using the example of comparison with the hydrolysate obtained by microbiological fermentation of the broiler chickens gizzard [10]. The values of physical-chemical indicators, as well as their standardized values according to GOST R 55334-2012 "Meat and meat-containing pates.…”
Section: Resultssupporting
confidence: 84%
“…Chicken meat is one of the important components of a healthy diet. It is a source of highquality, easily digestible proteins, vitamins, amino acids, and minerals, an essential component for the growth and functioning of the body, and the source of prevention of a number of diseases [17,18]. Poultry meat provides a complete balance of protein in the body among the majority of the population, thus the need for regular consumption of chicken meat becomes even more evident.…”
Section: Discussionmentioning
confidence: 99%
“…The protein fermentation by microorganisms led to the accumulation of several compounds, including exopolysaccharides, polyphenols, and bioactive peptides. These molecules played an important role in conferring antioxidant properties to the generated protein hydrolysates [36], and the ability to form film matrices. The literature has shown that marine polysaccharides, particularly sodium alginate, also possess inherent antioxidative properties through natural polyphenol content [5].…”
Section: Antioxidant Activity Of Alginate Filmsmentioning
confidence: 99%